Social Skill Training for the Social Problems among Adolescents with Specific Learning Disability - Joy, Molly; Augustine, Ann Mary (JOURNAL OF INDIAN EDUCATION, 2020)
The present research aimed to study the effectiveness of social skill training for the social problems among adolescents with Specific Learning Disability. Purposive sampling technique was used and the samples consisted of fourteen adolescents certified with Specific Learning Disability, aged between 12–15 years with lack of social skills. Pre-test was conducted using a parent version of social skill questionnaire (Spence, 1995) to assess the lack of social skills in adolescents with Specific Learning Disability. After the pre-test, social skill training was provided for the samples. A post-test was also done to check the effectiveness of the social skill training. Data were analysed using descriptive statistics, normality test and Paired sample t-test. Results obtained indicate that there is a significant difference between the pre-test score and post-test score of social problems among adolescents with specific learning disability. Findings thus reveal that social skill training found to be effective for the social problems among adolescents with Specific Learning Disability. Social skill training enhanced participant’s self-understanding and development of their strengths. Implications with respect to the provision of social support and interventions are discussed.